[SQRT(x + 3)] =1 + [SQRT(x - 2)]
I think. then you gotta do the rest.
Can someone helpe me solve this equation . Help me break it down please..becuase i have tried to do it mnay times but have fallen short...
[SQRT(x + 3)] - [SQRT(x - 2)] =1
2 answers
√(x+3) = 1 + √(x-2)
now square both sides
x+3 = 1 + 2√x-2) + x-2
2√x-2) = 4
√(x-2) = 2
square again
x-2 = 4
x = 6
check:
LS = √9 - √4
= 3-2 = 1 = RS
so x = 6
now square both sides
x+3 = 1 + 2√x-2) + x-2
2√x-2) = 4
√(x-2) = 2
square again
x-2 = 4
x = 6
check:
LS = √9 - √4
= 3-2 = 1 = RS
so x = 6